2015
DOI: 10.1007/s10714-015-1892-6
|View full text |Cite
|
Sign up to set email alerts
|

An exactly solvable inflationary model

Abstract: We discuss a model of gravity coupled to a scalar field that admits exact cosmological solutions displaying an inflationary behavior at early times and a power-law expansion at late times.Comment: 7 pages; several typos correcte

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…We expect that the exact solutions of simple models are useful to reveal some subtle features of the cosmological dynamical system [57][58][59][60][61][62][63][64][65][66][67]. Here, we investigate the cases with specific parameters, where the exact classical and quantum cosmological solutions can be obtained.…”
Section: Modified Positive-definite Actionmentioning
confidence: 99%
“…We expect that the exact solutions of simple models are useful to reveal some subtle features of the cosmological dynamical system [57][58][59][60][61][62][63][64][65][66][67]. Here, we investigate the cases with specific parameters, where the exact classical and quantum cosmological solutions can be obtained.…”
Section: Modified Positive-definite Actionmentioning
confidence: 99%
“…On the other hand, the cosmological duals of solitons interpolating between AdS in the infrared and scalecovariant geometries in the ultraviolet [28,29] may be relevant for describing inflation. It has been shown that the cosmological solutions of this class of models generate inflation as the scalar field rolls down from a de Sitter (dS) spacetime [36]. In this context, inflation can be described as an instability of the dS spacetime rolling down to a scaling solution.…”
Section: Arxiv:151004030v3 [Gr-qc] 2 Sep 2016mentioning
confidence: 99%
“…Notice that our notation differs from that of Ref [36]. for the units used and for a rescaling of the parameter µ by a factor of 2.…”
mentioning
confidence: 99%
“…Such accelerations can be caused by the dynamics of additional scalar modes in the Einstein gravity. In several models, exact solutions are known and thoroughly investigated [23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%